2013
DOI: 10.4103/2229-5186.115553
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and sleep associated problems in female pharmacy students

Abstract: Background: Sleep is an essential element for adolescent mental and physical growth and development, but today's young adolescents are deprived of this. Earlier studies in Europe and America showed pitiable sleep quality of young college students, which affect their academic growth. However, as per our literature search there is a lack of such studies in Indian context especially, within pharmacy education. Objective: The present study was designed to investigate the interrelation between the demographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…In this study, the overall sleep quality was very good, fairly good, fairly bad, very bad in 30.8%, 33.2%, 19.5%, and 16.5% of the subjects respectively. This result was higher than that of Vivek et al [28], in Banasthali University Rajasthan, India, where distribution of sleep quality were excellent 20.4%, good 38.5%, satisfactory 35.8%, poor 4%, very poor, 1.3%.…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, the overall sleep quality was very good, fairly good, fairly bad, very bad in 30.8%, 33.2%, 19.5%, and 16.5% of the subjects respectively. This result was higher than that of Vivek et al [28], in Banasthali University Rajasthan, India, where distribution of sleep quality were excellent 20.4%, good 38.5%, satisfactory 35.8%, poor 4%, very poor, 1.3%.…”
Section: Discussioncontrasting
confidence: 54%
“…Consistent with the results of previous studies reporting high rates of poor sleep quality, ranging from 31% to 84%, among nursing students (Aung et al, 2016;Desouky et al, 2015;Shamsaei and Cheraghi, 2009;Santos et al, 2016), we also found that male and female nursing students had a high prevalence of poor sleep quality (66.0% in male and 71.5% in female students). Poor sleep quality in nursing students can be attributed to various factors; for example, late-night study, long-term Internet use, stress induced by clinical situations, and coursework/examinations have been reported to induce the manifestation of poor sleep quality (Ghamdi, 2013;Jain et al, 2013;Sajadi et al, 2014; Table 2 Distributions of sleep disturbances in male and female nursing students. Zunhammer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…20 Finally, Jain et al found that subjectively-rated academic progress was one of the factors significantly correlated with sleep quality among female Indian pharmacy students, who reported frequent sleep-associated problems. 21 Questions remain regarding sleep quality of students in US colleges and schools of pharmacy. There is literature regarding undergraduate students' sleep in American colleges and universities, but the majority of literature regarding health professions students' sleep is from foreign universities, whose programs, students, and cultures can vary from those in the United States.…”
Section: Introductionmentioning
confidence: 99%